Workers' experiences of healthy work environment indicators at well-functioning primary care units in Sweden: a qualitative study - Kristina Areskoug Josefsson; Gunilla Avby; Monica Andersson Bäck; Sofia Kjellström (Taylor & Francis Group, 2018)
Objective: Staff experiences of healthy work environment (HWE) indicators at primary care units can assist in understanding why some primary care units function better than others. The aim of the study was to create increased understanding of how workers experienced HWE indicators at well-functioning primary care units. Design: Fifty in-depth interviews with staff at six primary care units in Sweden were analysed with deductive content analysis, revisiting a systematic review of HWE indicators. Results: The study presents additional perspectives on staff experiences of HWE indicators at well-functioning primary care units. The included primary care units (PCU) shared a similar pattern of work environment indicators, with unique solutions and strategies to meet shared challenges. Staff at the included PCUs were encouraged to work to create and sustain a HWE, but each domain (indicator) also provided challenges that the staff and organisation needed to meet. The results suggest that useful approaches for a healthy work environment could be to address issues of organisational virtuousness, employee commitment and joy at work. Conclusions: Both managers and staff are encouraged to actively work not only to create and sustain an HWE but also to promote organisational virtuousness, employee commitment, joy at work and to increase the performance at work, which is of benefit to staff, patients and society.Key Points Staff at well-functioning primary care units (PCUs) experienced healthy work environments The included PCUs shared a similar pattern of work environment indicators, with unique solutions and strategies to meet shared challenges. Staff at the included PCUs were encouraged to work to create and sustain a healthy work environment, but each domain (indicator) also provided challenges that the staff and organisation needed to meet. The results suggest that useful approaches for a healthy work environment could be to address issues of organisational virtuousness, employee commitment and joy at work.